2011
DOI: 10.1103/physrevx.1.021012
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Thermoelectric Properties of Sintered Compounds via High-ThroughputAb-InitioCalculations

Abstract: Several thousand compounds from the Inorganic Crystal Structure Database have been considered as nanograined, sintered-powder thermoelectrics with the high-throughput ab-initio AFLOW framework. Regression analysis unveils that the power factor is positively correlated with both the electronic band gap and the carrier effective mass, and that the probability of having large thermoelectric power factors increases with the increasing number of atoms per primitive cell. Avenues for further investigation are reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
211
0
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 161 publications
(220 citation statements)
references
References 69 publications
3
211
0
6
Order By: Relevance
“…However, as the band structure is expected to severely change in heavy doping, the rigid-band approximation would fail when Fermi-level is located more than 0.1 eV into the band edge. 24) We also checked the applicability of rigid-band approximation to the present Si-clathrate system, from the analysis on band structures of one electron and/or hole doped Si 46 and K 8 Ga 8 Si 38 . It was confirmed that changes of band structure could be characterized only by shifting the Fermi level, which was moved about 0.1 eV inside bands.…”
Section: Computational Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…However, as the band structure is expected to severely change in heavy doping, the rigid-band approximation would fail when Fermi-level is located more than 0.1 eV into the band edge. 24) We also checked the applicability of rigid-band approximation to the present Si-clathrate system, from the analysis on band structures of one electron and/or hole doped Si 46 and K 8 Ga 8 Si 38 . It was confirmed that changes of band structure could be characterized only by shifting the Fermi level, which was moved about 0.1 eV inside bands.…”
Section: Computational Proceduresmentioning
confidence: 99%
“…Chemical potentials ® i of element i were calculated as per atom energy in each primitive cell. Si 46 unit was used for the perfect cell throughout the calculation. It was confirmed that the difference in the formation energy between the unit cell and the 2 © 2 © 2 expanded supercell was about 0.1 eV.…”
Section: Computational Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition the CSTA has proven useful as a basis for performing high throughput searches for new thermoelectrics. [37][38][39] Going beyond the CSTA would require detailed knowledge of the energy dependent scattering mechanisms including different sources of scattering in combination. For example, if one includes only acoustic phonon scattering with τ −1 proportional to the density of states, one obtains the result that the mobility diverges and the conductivity is flat as the carrier concentration is lowered to zero.…”
mentioning
confidence: 99%
“…[6][7][8][9] Likewise, the tools and software packages, such as density functional theory (DFT), 10,11 for simulated experiments have improved by considering simplified models and potentials, 7,[12][13][14] as well as preliminary screening techniques [15][16][17][18] making high-throughput computational modeling more viable.…”
Section: Introductionmentioning
confidence: 99%